An Integrative TPB-SCCT Analysis of Generation Z’s Intention in Continuing Family Business: A Qualitative Study in a Private University - I Gusti Ayu Agung Istri Dinda Larasshanti Jelantik (Green Publisher Indonesia, 2025)
This study aims to explore the entrepreneurial intention of Generation Z students to continue their family businesses, focusing on the underlying cognitive and motivational factors that shape these intentions. A qualitative research design was adopted, employing in-depth interviews with eight generation Z undergraduates’ students from Universitas Pendidikan Nasional (Undiknas), Bali. Respondents were selected through purposive sampling and met specific criteria. The study integrates Theory of Planned Behavior (TPB) and Social Cognitive Career Theory (SCCT) as dual theoretical lenses. Data were analyzed using Mayring’s content analysis to identify recurring themes and theoretical linkages. The finding reveals three key themes influencing Gen Z students’ intention: family influence, economic and perceived benefit, and intrinsic factors. This study also discovers the communication process is a factor that support the intention toward entrepreneurship. The integration of TPB and SCCT provides multidimensional understanding the cognitive evaluations and motivational belief interact in shaping entrepreneurial intentions. Although conducted in Bali, this study did not deeply examine the influence of Balinese cultural values, suggesting an opportunity for future research to incorporate cultural dimension into family business succession studies.